2018
DOI: 10.21037/jtd.2018.01.156
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery pathways in thoracic surgery: the Quebec experience

Abstract: Background: Canada has a universal public health system where all resources must be allocated to optimize cost-effectiveness. Rapid diagnostic assessment programs (DAPs) and enhanced recovery protocols Conclusions: DAPs and ERPs have promising roles in thoracic surgical practice. A rapid DAP can expedite the care trajectory of patients with lung cancer and has allowed our institution to adhere to governmental standards for the management of lung cancer. ERPs are feasible to establish and can effectively improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Rapid diagnostic assessment programs (DAPs) and enhanced recovery protocols (ERPs) may improve timeliness of surgical care [ 3 ]. Dr. Hubert and colleagues reported that using the DAP, the median time between the patient’s first clinic visit and referral to surgery was 30 days, and the median time between surgical consult and treatment was 29 days [ 24 ]. To date, there is no consensus whether a longer preoperative delay has a negative effect on overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid diagnostic assessment programs (DAPs) and enhanced recovery protocols (ERPs) may improve timeliness of surgical care [ 3 ]. Dr. Hubert and colleagues reported that using the DAP, the median time between the patient’s first clinic visit and referral to surgery was 30 days, and the median time between surgical consult and treatment was 29 days [ 24 ]. To date, there is no consensus whether a longer preoperative delay has a negative effect on overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Regarding thoracic surgery, there are different comparable ERATS protocols (with similar, but not the same recommendations) developed from different centers in different countries. [ 9 10 11 12 13 14 15 16 17 ] The Enhanced Recovery After Surgery (ERAS®) Society and the European Society of Thoracic Surgeons (ESTS) have subsequently developed an international “formal” consensus on ERATS. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Immediately upon arrival to the PACU an attempt is made to move the patient from the stretcher to the chair. This is a marked difference from published ERAS protocols for thoracic surgery; in fact, we were able to find only a single program which reported a goal of mobilization to a chair prior to four hours post-surgery (8). If this is deemed unsafe by nursing staff, (e.g., if the patient is unable to mentate or the vitals are tenuous) then an attempt is made every 3-5 minutes thereafter.…”
Section: Pacumentioning
confidence: 80%
“…Additional challenges unique to thoracic surgery include the physiologic insult caused by one lung ventilation intraoperatively and pain from intercostal incisions limiting respiratory effort. There are currently no consensus guidelines from the ERAS group for general thoracic surgery; however, several groups have published their initial experiences with enhanced recovery protocols (3)(4)(5)(6)(7)(8)(9)(10). Common elements include preoperative optimization with smoking cessation and preoperative exercise regimens, intraoperative care modifications with a focus on minimally invasive techniques, drain limitation, and long term narcotic avoidance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation